Shifting the mindset culture to address global educational disparities - Cameron A. Hecht; Mary C. Murphy; Carol S. Dweck; Christopher J. Bryan; Kali H. Trzesniewski; Fortunato N. Medrano; Matt Giani; Pratik Mhatre; David S. Yeager (npj Science of Learning, 2023)
Abstract Educational outcomes remain highly unequal within and across nations. Students’ mindsets—their beliefs about whether intellectual abilities can be developed—have been identified as a potential lever for making adolescents’ academic outcomes more equitable. Recent research, however, suggests that intervention programs aimed at changing students’ mindsets should be supplemented by programs aimed at the changing the mindset culture, which is defined as the shared set of beliefs about learning in a school or classroom. This paper reviews the theoretical and empirical origin of the mindset culture and examines its potential to reduce group-based inequalities in education. In particular, experiments have identified two broad ways the mindset culture is communicated by teachers: via informal messages about growth (e.g., that all students will be helped to learn and succeed), and formal opportunities to improve (e.g., learning-focused grading policies and opportunities to revise and earn credit). New field experiments, applying techniques from behavioral science, have also revealed effective ways to influence teachers’ culture-creating behaviors. This paper describes recent breakthroughs in the U.S. educational context and discusses how lessons from these studies might be applied in future, global collaborations with researchers and practitioners.